Microarchitected 3D printed polylactic acid (PLA) nanocomposite scaffolds for biomedical applications. (March 2020) - Alam, Fahad; Shukla, Vishnu Raj; Varadarajan, K.M.; Kumar, S.
Abstract: Anti-bacterial scaffolds made of copper, bronze and silver particles filled PLA nanocomposites were realized via fused filament fabrication (FFF), additive manufacturing. The thermal, mechanical and biological characteristics including bioactivity and bactericidal properties of the scaffolds were evaluated. The incorporation of bronze particles into the neat PLA increases the elastic modulus up to 10% and 27% for samples printed in 0° and 90° configurations respectively. The stiffness increases, up to 103% for silver filled PLA nanocomposite scaffolds. The surface of scaffolds was treated with acetic acid to create a thin porous network. Significant increase ( 20–25%) in the anti-bacterial properties and bioactivity ( 18–100%) is attributed to the synergetic effect of reinforcement of metallic/metallic alloy particles and acid treatment. The results indicate that PLA nanocomposites could be a potential candidate for bone scaffold applications. Graphical abstract: Image 1 Highlights: Anti-bacterial metal/alloy filled PLA nanocomposite scaffolds could be a potential candidate for biomedical applications. Metal/alloy particles increases the elastic modulus up to 10% (0°, PLA-Br) and 27% (90°, PLA-Br). Significant increase in the anti-bacterial ( 20–25%) properties was observed due to reinforcement of metal/alloy particles. Acid treatment of the scaffolds enhanced bioactivity for all samples and maximum increase was observed for PLA-Cu ( 100%).